2014
DOI: 10.3389/fmicb.2014.00304
|View full text |Cite
|
Sign up to set email alerts
|

Application of calcifying bacteria for remediation of stones and cultural heritages

Abstract: Since ages, architects and artists worldwide have focused on usage of durable stones as marble and limestone for construction of beautiful and magnificent historic monuments as European Cathedrals, Roman, and Greek temples, Taj Mahal etc. But survival of these irreplaceable cultural and historical assets is in question these days due to their degradation and deterioration caused by number of biotic and abiotic factors. These causative agents have affected not only the esthetic appearance of these structures, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 89 publications
0
81
2
2
Order By: Relevance
“…Our composite material can be deposited on‐site since its production does not require the use of complex instruments, and its chemical resistance is predicted to be comparable to that of other calcium carbonate‐based coatings, which offer excellent protection against chemical degradation and weathering. Our bacterial composites are therefore promising for applications, for example, in civil engineering for crack prevention or remediation in biocement, in CO 2 sequestration, in the automotive and aerospace industries for the production of lightweight structural components, as protective coatings for dust or erosion control, or for conservation of ornamental stone or cultural heritage items …”
mentioning
confidence: 99%
“…Our composite material can be deposited on‐site since its production does not require the use of complex instruments, and its chemical resistance is predicted to be comparable to that of other calcium carbonate‐based coatings, which offer excellent protection against chemical degradation and weathering. Our bacterial composites are therefore promising for applications, for example, in civil engineering for crack prevention or remediation in biocement, in CO 2 sequestration, in the automotive and aerospace industries for the production of lightweight structural components, as protective coatings for dust or erosion control, or for conservation of ornamental stone or cultural heritage items …”
mentioning
confidence: 99%
“…One common natural occurring biomineralization process is the microbial carbonate precipitation, which has been vastly studied and described in different environments (such as caves, soils, sediments, aquifers and open-water areas) as playing an important role in the cementation of these ecosystems (Boquet et al, 1973; Cañveras et al, 2001; Banks et al, 2010; Chou et al, 2011). Over the past few years, microbial carbonate precipitation has emerged as a promising method for conservation and restoration of limestone artwork by offering multiple advantages in comparison with traditional procedures (Le Métayer-Levrel et al, 1999; Dhami et al, 2014b). Although it has been shown that limestone could be consolidated by applications of culture media inoculated with the desirable bacterial strains (i.e., with high carbonatogenetic ability and that produce a precipitate similar to the substrate) such as Myxococcus xanthus (Rodriguez-Navarro et al, 2003) and some Pseudomonas and Bacillus species (Cameotra and Dakal, 2012), a more advantageous method relies on using the resident microbiota that has the ability to induce calcium carbonate precipitation (Ettenauer et al, 2011; Jroundi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As Bacteria represent the first and most diverse group of microorganisms that colonize ornamental stone, understanding their communities’ spatial distribution, structure and composition may lead to the development of more efficient conservation and restoration strategies (Cameotra and Dakal, 2012). Furthermore, the isolation and characterization of microbial strains dwelling on limestone monuments may provide the necessary means for envisioning environmentally friendly preservation methods based on biomineralization (i.e., carbonate bioprecipitation) (Jroundi et al, 2012; Dhami et al, 2014b; López-Moreno et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of historically and culturally significant monuments, stone structures, documents, and artworks is of growing concern [16]. Exposure to the outdoor environment or to uncontrolled indoor environments (temperature and relative humidity) leads to deterioration largely due to atmospheric pollution from a variety of contaminants, including nitrates, sulfates, black crusts, organic matter, and microorganisms [16,[80][81][82][83]. Deterioration is a complex process involving chemical, physical, and biological mechanisms.…”
Section: Cleaning Of Historical Art Objects and Structuresmentioning
confidence: 99%